Sistem Pengarsipan Data Berbasis Web Pada Kelurahan Oetete, Kota Kupang Menggunakan Framework Laravel - Gede Abdi Candrawira Wicaksana; Evangs Mailoa (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
This research takes a case study at Oetete, Kupang City, East Nusa Tenggara. The problems faced are archival documents which are susceptible to damage, being scattered or lost, as well as the time required to archive which takes approximately four days because there are seventeen document categories and data archiving is carried out using print or paper media. There are also other factors such as termites and inadequate archive storage. The output of this research is a web-based document archiving system created using the PHP programming language and the Laravel framework. With this web-based archiving system, it is hoped that it can help with data archiving problems in Oetete, Kupang City, East Nusa Tenggara.